Identifying the Barriers and Opportunities in the Provision and Use of Weather and Climate Information for Flood Risk Preparedness: The Case of Katakwi District, Uganda - Mitheu, Faith; Petty, Celia; Tarnavsky, Elena; Stephens, Elisabeth; Ciampi, Luisa; Butsatsa, Jonah; Cornforth, Rosalind (Frontiers in Climate, 2022)
The provision of weather and climate information (WCI) can help the most at-risk communities cope and adapt to the impacts of extreme events. While significant progress has been made in ensuring improved availability of WCI, there remain obstacles that hinder the accessibility and use of this information for adaptation planning. Attention has now focused on the “usability gap” to ensure useful and usable WCI informs practise. Less attention has however been directed on barriers to the active production and use of WCI. In this study, we combine two frameworks through a bottom-up approach to present a more coordinated institutional response that would be required to ensure a better flow of information from information providers to users at community level and vice versa. The bottom-up approach was designed in form of Farmers Agri-Met Village Advisory Clinics (FAMVACs) and Listening Groups (LG) and was initiated by Uganda Meteorological Authority (UNMA) as a way of ensuring connections between the information providers, the disseminators, and the communities to specifically give voice to the communities to provide feedback on the use of WCI in coping with flood risks. This approach is used to identify the barriers and opportunities in the production/provision and use of WCI for flood risk preparedness for a case study in Eastern Uganda. First, a use-case is developed for Katakwi District where smallholder farming communities have recorded their coping practises and barriers to the use of WCI in practise. Second, online interviews with practitioners from disaster management institutions are used to identify barriers to the production and provision of WCI to local farming communities. Findings show that for providers, barriers such as accessibility and completeness of data hinder the production of useful WCI. In situations where useful information is available, technical language used in the format and timeliness in dissemination hinder usability by local farmers. Useful and usable WCI may not be acted on in practise due to factors such as costs or market availability e.g., lack of access to improved seeds. Further, the study highlights possible solutions to bridge the identified gaps and they include capacity building, fostering data collaborations across sectors, data translation to simple advisories, among others. The study also presents the FAMVACs approach which shows the importance of a more coordinated response with a shift of focus from the users of information only, to a more inclusive understanding of the data and information gaps across the wider provider-user landscapes. We argue that this would contribute to more effective disaster management at both the national and local levels.